(untitled) (Scientific journal of the Fergana State University, 2023)
The article provides new information on the biological characteristics of the entomophagous lacewing (Chrysopidae: Chrysoperla) in the Fergana Valley. The studies were carried out in the conditions of the Fergana region during 2020-2021. Larvae and adults of goldenrod were observed in nature and in biolaboratory conditions. When collecting insects and their entomophages, as well as compiling collections, generally accepted entomological methods were used. Data on the biology and ecological features of insects were subjected to a comparative analysis in the works of other authors. On the basis of the collected materials, the morphometric features, color and size of the leaves, the life cycle of the tricolor common centaury in the conditions of the Ferghana Valley are described. The data on the artificial keeping and effective use of the Altynkuz entomophage in laboratory conditions are presented.